Genome of Kumamoto Oyster Crassostrea sikamea Provides Insights Into Bivalve Evolution and Environmental Adaptation - Sheng Liu; Youli Liu; Ximing Guo; Naoki Itoh; Guangqiu Chang; Zhihua Lin; Qinggang Xue (Evolutionary Applications)
ABSTRACT The Kumamoto oyster, Crassostrea sikamea, is a marine bivalve naturally distributed along the coasts of southern China and southern Japan, with a hatchery population that has been under domestication in the United States since its introduction from Japan in the 1940s. To understand its evolutionary history and environmental adaptation, we produced a chromosome‐level genome assembly of C. sikamea and conducted whole‐genome resequencing of 141 individuals from the US hatchery population and six wild populations from China and Japan. The assembled genome of C. sikamea has a size of 616 Mb covering all 10 chromosomes with a contig N50 of 4.21 Mb and a scaffold N50 of 62.25 Mb. Phylogenetic analysis indicated that C. sikamea diverged from the Crassostrea angulata and Crassostrea gigas clade about 9.9 million years ago. Synteny analysis revealed significant chromosomal rearrangements during bivalve evolution leading to oysters, but remarkable conservation of all 10 oyster chromosomes over ~180 million years, a surprising disparity in chromosomal evolution. Phylogenetic analysis produced three distinct clusters for the US, Japanese, and Chinese populations, with the US population closer to the Japanese population, confirming its origin. No differentiation was detected among the five Chinese populations, indicating strong gene flow. Between the US and Japan populations, 402 genes exhibited selection signals, including three myosin heavy chain genes that were also differentiated in domesticated lines of the eastern oyster, suggesting changes in these genes may be important for domestic production. Among the 768 genes showing selection signals between natural populations of Japan and China, genes related to stress response are most enriched, suggesting responding to environmental stress is critical for local adaptation. These findings provide insights into bivalve evolution and environmental adaptation, as well as useful resources for comparative genomics and genetic improvement of cultured Kumamoto oyster stocks.